Development of Active and Fun Learning-Based Educational Videos to Enhance Communication Skills and Students’ Independence Learning - Nurliya Mufarrochah; I Wayan Wesa Atmaja; Hariyanto Hariyanto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop and test the effectiveness of educational videos based on Active and Fun Learning in improving students' communication skills and learning independence. The problem behind this study is the low level of student interaction and motivation in conventional learning processes. This study used a research and development (R&D) method using a development model developed by Thiagarajan (4D: Define, Design, Develop, Disseminate). 32 eighth-grade students at SMPN 11 Jember as the research subjects. Data were collected through expert validation, student response questionnaires, and communication skills tests. The instruments were processed using quantitative descriptive methods. The results of the media expert validation showed an average of 94.67% (very feasible category), while the material expert validation showed a result of 93.33% (very feasible category). The effectiveness test results showed a significant increase in students' communication skills with an average N-gain value of 0.71 (high category). In addition, the questionnaire results showed an increase in learning independence with the majority of students in the high category. It can be concluded that Active and Fun Learning-based educational videos are effective as innovative learning media to improve the quality of learning, especially in the aspects of communication and student learning independence